PELAKSANAAN PROGRAM PENGEMBANGAN KEWIRAUSAHAAN PEMUDA OLEH DINAS PEMUDA DAN OLAHRAGA KOTA PEKANBARU TAHUN 2017 - Ramadhan, Abdul Hafil; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
In 2017 the City of Youth and Sports Agency in Pekanbaru organized entrepreneurship training activities for young people, which was attended by 25 young people. The reason for the low number of participants is the lack of socialization from the organizers of activities and the lack of funds allocated for activities. As a series, it does not stop with training activities and apprenticeship activities, but also continues with mentoring, mentoring, partnership and promotion activities. and capital access assistance. Formulation of the research problem: how is the implementation of youth entrepreneurship development programs by the Pekanbaru City Youth and Sports Office in 2017? The purpose of the research: to find out the implementation of youth entrepreneurship development programs by the Pekanbaru City Youth and Sports Department in 2017. To find out the inhibiting factors in the implementation of youth entrepreneurship development programs by the Pekanbaru City Youth and Sports Department in 2017. Primary data sources through interviews and secondary data sources . The data analysis technique was carried out with a qualitative descriptive analysis.The interests of the Pekanbaru City Government are the interests in implementing the rules and realizing the vision and mission, while the youth have an interest in increasing their ability and creativity in entrepreneurship. The benefits are motivated to entrepreneurship, a lot of knowledge is known about the world of entrepreneurship, have experience because of taking part in apprenticeship, and increasing the number of people known. The desired degree of change is that unemployment can be reduced. Decision makers are adjusted to the level of hierarchy in the Pekanbaru City Youth and Sports Agency. The resources mobilized in the form of human resources from the apparatus who work in the Department of Youth and Sports of the City of Pekanbaru, the total financial resources are taken from regional finance, technology resources and facilities and infrastructure, all of which are inventory. The inhibiting factor is the lack of youth involved and the bureaucratic characteristics prevailing in government institutions. Keywords: Implementation, Policy Implementation